Low-Temperature Methane Partial Oxidation over Pd Supported on CeO2: Effect of the Preparation Method and Precursors - Shiva Fazlikeshteli; Xavier Vendrell; Jordi Llorca (Reactions, 2021)
The catalytic production of syngas by the partial oxidation of methane (POM) was investigated over Pd supported on ceria (0.5–2 Pd wt.%) prepared by incipient wetness impregnation and by mechanochemical methods. The performance of the Pd/CeO2 catalyst prepared by milling CeO2 and Pd acetate was superior to that prepared by milling CeO2 and Pd nitrate and to Pd/CeO2 prepared by impregnation from Pd acetate. The best catalytic activity of the Pd/CeO2 catalyst prepared from CeO2 and Pd acetate was obtained by milling at 50 Hz for 5 min. Two-step combustion and reforming reaction mechanism were identified. Remarkably, methane conversion increased progressively with Pd loading for the catalysts prepared by incipient wetness impregnation, whereas low metal loading showed better conversion of methane for the catalysts prepared by ball milling using Pd acetate. This was explained in terms of an impressive dispersion of Pd species with a strong interaction with the surface of ceria, as deduced from transmission electron microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy characterization, which revealed a large quantity of highly oxidized species at the surface.